Do the variations in renal pelvic angles play a role in the formation of renal stone? A computed tomography study. (21st October 2015) - Sanal, Bekir; Korkmaz, Mehmet; Can, Fatma; Aras, Bekir; Buyukkaya, Ayla
Abstract: Objective : In this study, we aimed to investigate the effect of variations in renal pelvic angle on urinary calculi development. Materials and methods : A total of 2456 unenhanced abdominal CT scans were retrospectively evaluated and 262 kidneys of 131 patients were compared. Patients included in this study were identified and qualified as follows: Having unilateral calculi, having no calculi or a history of calculi in contra-lateral side and having totally normal renal morphology. Results : The mean angle of kidneys with calculi was 55 ± 9°, while the average angle measurement was 61 ± 11° in kidneys without calculi. The mean angle measured from the kidneys with calculi was statistically smaller ( p  < 0.001). Conclusion : Our study suggests that the possibility of calculi development in kidneys, which have more anteriorly localized pelvic angulation tends to be significantly higher in individuals, who did not have any congenital or acquired renal pathology before.